Online or In-Person Instruction? Factors Influencing COVID-19 Schooling Decisions Among Latinx Families in Houston, Texas - Julia Szabo (SAGE Publishing, 2021)
Throughout the COVID-19 pandemic, families have faced a difficult decision between online and in-person instruction. In many school districts, a higher proportion of non-White families selected online instruction for fall 2020, but the factors influencing these patterns are unclear. Using a case study approach, I focus on the experiences of 21 Latinx families whose children attend the same majority-Latinx charter school in Houston, Texas, and explore the factors families balanced when deciding between online and in-person instruction. Drawing on 37 in-depth interviews with mothers and their children, I find that Latinx families made schooling decisions informed by their shared school context, the needs of family networks, and community infection rates. Health and safety concerns drove most families to select online instruction while acknowledging it was an academic sacrifice, but maternal employment and access to child care shaped their ability to make this choice. This study highlights the influence of nonschool factors in pandemic schooling decisions.